Karakteristik Segmen Gen sitokrom C Oksidase Subunit I (COI) Ngengat Plusia chalcites (Lepidoptera: Noctuidae) - Suriana Suriana; Marwansyah Marwansyah; Amirullah Amirullah (University of Halu Oleo, 2019)
ABSTRACTThe research was exploration ofpartial COI gene of moth (Plusia chalcites).The aim of this research is to characterization of nucleotide sequence of these COI gene, that was exracted with Cetyl Trimetyl Ammonium Bromide (CTAB) method, and then amplified by Polymerase Chain Reaction (PCR) technique with spesifik primer. The result PCR amplified subsequent analysis of nitrogen base arrangement in these COI gene. The analysis data using the BioEdit and MEGA Version 5.0 software.The results showed that the segment of COI gene in Plusia chalcites as long 710 bp (base pairs). From these, there are 503/657 nucleotides which are conserved, 154/657 nucleotides of varies, 124/657 parsimoni informative nucleotides and 30/657 singeleton nucleotides. The base N composition consist of 39.0% Timine, 14.0% Cytosin (C), 31.7%Adenine (A) and 15.4% Guanin.Key words: Plusia chalcites, COI Gene characteristics and composition. ABSTRAK Penelitian ini merupakan penelitian eksplorasi untuk mengkarakterisasi sekuen gen COI. Karakterisasi gen COI meliputi isolasi DNA menggunakan metode CTAB (Cetyl Trimetyl Ammonium Bromide), amplifikasi gen COI dengan teknik PCR (Polymerase Chain Reaction) dan squencing untuk analisis susunan basa nitrogen pada gen COI. Analisis data molekuler menggunakan software BioEdit dan MEGA Version 5.0.Hasil penelitian menunjukkan segmen gen COI Plusia chalcites yang teramplifikasi berukuran 710 pb, dan terkarakterisasi sepanjang 657pb. Dari segmen tersebut terdapat 503/657 nukleotida yang bersifat conserved (kekal), 154/657 nukleotida yang bersifat variabel (bervariasi), 124/657 nukleotida parsimoni informative dan 30/657 nukleotida singleton. Komposisi basa nitrogen sekuen gen COI Plusia chalcites yaitu Timin (T) 39,0%, Cytosin (C) 14.0%, Adenin (A) 31,7% dan Guanin 15,4%. .Kata kunci :Plusia chalcites, Karakteristik Gen COI